PENGELOLAAN ZAKAT PRODUKTIF BADAN AMIL ZAKAT NASIONAL (BAZNAS) MANDAILING NATAL (MADINA) - Misbah Mardiah (Institut agama islam negeri Padangsidimpuan, 2019)
Productive zakat of madina baznas that has required mustahik to return the productive zakat funds that have been given mustahik viewed in terms of islamic law and rules governing zakat management. Research of this thesis is classified as a type of field research or qualitative method. Then, this research uses a normative research approch means the result of primary data is using zakat management by perspective of Yusuf Qurdawi, decree of MUI number 14 year 2011 and laws number 23 year 2011. The procedure that is done baznas of mandailing natal to mustahik should be recomended by the head of village, have permisson from KUA. After obtaining the permission all requirments, than mustahik can apply to obtain productive zakat. Baznas should pay attention to coaching program to mustahik also, not only as an authorized capital but also a provider and a mentor training, the aim is provide insight for mustahik better. In this case, Baznas does not provide training and mentoring to mustahik. If viewed from Baznas program give capital to mustahik that already has a small business and already has a small business and individual system, are not a group. The baznas should give the hinghes capital of the already channeled capital and form a group system, because according to the authors better a group system, so it can unify the idea of the mustahik and easier to succeed that business. As for management of Baznas productive zakat is very good, when viewed in terms of purpose of Baznas is to eradicate the proverty of Madina citizens. Management of baznas productive zakat in Mandailing Natal, viewed from the perspective by Yusuf Qurdawi, the decision of MUI fatwa, law number 23 year 2011, Baznas does not violate management of productive zakat mustahik, they only choose poor people. Students and fakir should be categorized in the receipt of productive zakat.